Designing Evolvable Location Models for Ubiquitous Applications - Gordillo, Silvia Ethel (2003)
In this paper we present an object-oriented approach for building location models in the context of ubiquitous applications. We first motivate our research by discussing which design problems we face while building this kind of applications; we stress those problems related with applications’ evolution. We then present a set of simple design micro-architectures for representing locations and their interpretation. We finally discuss some further research work.